The Role of E-Commerce in the Success of Small and Medium Enterprises - Z N P Andeka; Berny Indrawan (Journal of Business and Behavioural Entrepreneurship, 2021)
This study aims to analyze the role of e-commerce in business success in Coblong District. The method in this study used a qualitative analysis method with a case study model. This study used four micro-scale entrepreneurs who use e-commerce in conducting their business as research objects. The analysis process is based on the role of e-commerce in Small and Medium Enterprises (SMEs) in Coblong District. Based on the results of the study, it can be concluded that in general e-commerce has a role that can help entrepreneurs including small and medium businesses to improve their business development. These roles include the ease of communication, marketing, minimal capital, and time efficiency. The analysis also shows that the respondents still use e-commerce for the role they have.